Optimalisasi Parameter Pada Mesin CNC Milling Terhadap MRR Menggunakan Material S50C Dengan Metode Taguchi - Afgi Finofal; Eko Yudo; Sukanto Sukanto (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
This study aims to analyze the effect of process parameters on the Material Removal Rate (MRR) in CNC milling machining of S50C steel material. The process parameters examined include spindle speed (RPM), cutting speed (Vc), and depth of cut. The experimental design uses the Taguchi method with an L9 (3³) Orthogonal Array matrix, including three repetitions to ensure data reliability. The analysis results show that the depth of cut has the most significant impact on increasing MRR, contributing 86.14%. The optimal MRR value is achieved with the process parameter combination of spindle speed at 3,184 rpm, cutting speed at 105 m/min, and depth of cut at 0.6 mm. Selecting the appropriate process parameters can enhance the efficiency of material removal in CNC milling machining. This research provides guidance for practitioners to determine optimal parameters to achieve maximum results in material processing.